Petrography of low-grade metamorphic rocks of the Lesser Himalaya from Malekhu area, central Nepal - Acharya, Rajendra; Paudyal, Kabiraj (Journal of Science and Engineering, 2015)
Petrographic study was carried out in the rocks of the Nawakot Group from the Malekhu area. Representative samples from all the units were collected systematically. The area is occupied by low-grade metamorphic rocks of the Lesser Himalaya. The main lithology of this study area consists of phyllite, quartzite, metasandstone, dolomite, slate and metabasics. The main aim of this study was to distinguish the individual rock types based on the petrographic characteristics. Necessity of this type of study is felt because about each geological unit has similar type of rocks. In the case of complex geological setting due to faults and thrusts, distinction between the macroscopically similar rocks is possible only under the thin sections. Keeping this geological problem in mind, altogether 12 thin sections of representative rocks were prepared and studied for mineral paragenesis, texture, microscopic structures, deformation characteristics and metamorphic grade. Chlorite is found in all pelitic rocks as a metamorphic index mineral.